Chromophore Induced Effects in Iron(III) Complexes - Schmitz, Lennart; Argüello Cordero, Miguel A.; Al-Marri, Mohammed J.; Schoch, Roland; Egold, Hans; Neuba, Adam; Steube, Jakob; Bracht, Bastian Johannes; Bokareva, Olga S.; Lochbrunner, Stefan; Bauer, Matthias (Inorganic Chemistry)
In the search for noble metal free photocatalytic systems, iron is the dream candidate. To increase excited state lifetimes of iron complexes, the multichromophoric approach is promising, combining organic chromophores with photoactive iron complexes, potentially enabling a reservoir effect. We present a series of chromophore-functionalized complexes based on the parental FeIII complex [Fe(ImP)2][PF6] (HImP = 1,1′-(1,3-phenylene)bis(3-methyl-1-imidazole-2-ylidene)). The four organic chromophores benzene, naphthalene, anthracene, and pyrene are attached to the ImP-ligand in para-position to the coordination site to systematically investigate the influence of the steric demand and electronic properties of the chromophore on charge transfer lifetimes as well as photodynamics. A thorough ground state characterization was conducted in addition to investigations of the excited state dynamics by transient absorption spectroscopy and streak camera emission measurements. The conclusions drawn are supported by extensive DFT calculations. The emission coefficients could be significantly improved by the addition of chromophores. After excitation of the complexes with larger chromophores, coplanarization of the backbone and complex motif occurs to stabilize the formal charge. This results in population of a superligand state that exhibits a much faster radiationless relaxation to the ground state compared to the parent complex, hindering a reservoir effect.
Keywords: Photo

Low Temperature Emissive Cyclometalated Cobalt(III) Complexes - Krishna, Athul; Fritsch, Lorena; Steube, Jakob; Argüello Cordero, Miguel A.; Schoch, Roland; Neuba, Adam; Lochbrunner, Stefan; Bauer, Matthias (Inorganic Chemistry)
A series of CoIII complexes [Co(RImP)2][PF6], with HMeImP = 1,1′-(1,3-phenylene)bis(3-methyl-1-imidazole-2-ylidene)) and R = Me, Et, iPr, nBu, is presented in this work. The influence of the strong donor ligand on the ground and excited-state photophysical properties was investigated in the context of different alkyl substituents at the imidazole nitrogen. X-ray diffraction revealed no significant alterations of the structures and all differences in the series emerge from the electronic structures. These were probed via cyclic voltammetry and UV–vis spectroscopy, detailing the influence of the different alkyl substituents on the ground-state properties. All complexes are emissive at 77 K from a 3MC state, which exhibits lifetimes in the range of 1–5 ns at room temperature, depending on the alkyl substituent. Therefore, it is clearly shown that even small differences in the electronic structure have a large impact on the details of the excited state landscape. The observed behavior was rationalized by a detailed DFT analysis, which shows that the minimum-energy crossing point to the ground-state is located only slightly above the MC energy: Consequently, nonradiative decay to the ground state at room temperature is enabled, while at 77 K this path is prohibited, leading to low-temperature 3MC emission.
Keywords: Photo

A Comparative Kinetic and Computational Investigation of the Carbon‐Sulfur Cross Coupling of Potassium Thioacetate and 2‐Bromo Thiophene Using Palladium/Bisphosphine Complexes - Peschtrich, Sebastian; Schoch, Roland; Kuckling, Dirk; Paradies, Jan (European Journal of Organic Chemistry)
Abstract We conducted an investigation into the palladium‐catalyzed carbon‐sulfur cross‐coupling reaction involving a 2‐bromothiophene derivative and potassium thioacetate as a substitute for hydrogen sulfide. This investigation utilized kinetic and computational methods. We synthesized two palladium complexes supported by the bisphosphane ligands bis(diphenylphosphino)ferrocene (DPPF) and bis(diisopropylphosphino)ferrocene (D i PPF), as well as their tentative intermediates in the catalytic cycle. Reaction rates were measured and then compared to computational predictions.
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Synthesis of Ferrocenyl Boranes and their Application as Lewis Acids in Epoxide Rearrangements - Köring, Laura; Birenheide, Bernhard; Krämer, Felix; Wenzel, Jonas O.; Schoch, Roland; Brehm, Martin; Breher, Frank; Paradies, Jan (European Journal of Inorganic Chemistry)
A series of substituted ferrocenyl boron derivatives was synthesized. The oxidation of the ferrocenyl unit resulted in a significant increase of the boron‐centered Lewis acidity. The neutral and cationic Lewis acids were characterized by NMR‐spectroscopy, crystal structure analysis and by computational methods. The new Lewis acids were then applied in the Meinwald rearrangement of epoxides, predominantly furnishing aldehydes as the kinetic products.
Keywords: Inorganic Chemistry

Isostructural Series of a Cyclometalated Iron Complex in Three Oxidation States - Steube, Jakob; Fritsch, Lorena; Kruse, Ayla; Bokareva, Olga S.; Demeshko, Serhiy; Elgabarty, Hossam; Schoch, Roland; Alaraby, Mohammad; Egold, Hans; Bracht, Bastian Johannes; Schmitz, Lennart; Hohloch, Stephan; et al. (Inorganic Chemistry)
An isostructural series of FeII, FeIII, and Fe(IV)complexes [Fe(ImP)2]0/+/2+ utilizing the ImP 1,1′-(1,3-phenylene)-bis(3-methyl-1-imidazol-2-ylidene) ligand, combining N-heterocy-clic carbenes and cyclometalating functions, is presented. The strong donor motif stabilizes the high-valent Fe(IV) oxidation state yet keeps the FeII oxidation state accessible from the parent Fe(III)compound. Chemical oxidation of [Fe(ImP)2]+ yields stable [FeIV(ImP)2]2+. In contrast, [FeII(ImP)2]0, obtained by reduction,is highly sensitive toward oxygen. Exhaustive ground state characterization by single-crystal X-ray diffraction, 1H NMR,Mössbauer spectroscopy, temperature-dependent magnetic measurements, a combination of X-ray absorption near edge structureand valence-to-core, as well as core-to-core X-ray emission spectroscopy, complemented by detailed density functional theory (DFT) analysis, reveals that the three complexes[Fe(ImP)2]0/+/2+ can be unequivocally attributed to low-spin d6, d5, and d4 complexes. The excited state landscape of the Fe(II) and Fe(IV) complexes is characterized by short-lived 3MLCT and 3LMCT states, with lifetimes of 5.1 and 1.4 ps, respectively. In the FeII-compound, an energetically low-lying MC state leads to fast deactivation of the MLCT state. The distorted square-pyramidal state, where one carbene is dissociated, can not only relax into the ground state, but also into a singlet dissociated state. Its formation was investigated with time-dependent optical spectroscopy, while insights into its structure were gained by NMR spectroscopy.
Keywords: Photo

Insights into the First Multi-Transition-Metal Containing Ruddlesden Popper-Type Cathode for all-solid-state Fluoride Ion Batteries - Vanita, Vanita; Waidha, Aamir Iqbal; Vasala, Sami; Puphal, Pascal; Schoch, Roland; Glatzel, Pieter; Bauer, Matthias; Clemens, Oliver (Journal of Materials Chemistry A)
Promising cathode materials for fluoride-ion batteries (FIBs) are 3d transition metal containing oxides with Ruddlesden-Popper-type structure. So far, multi-elemental compositions were not investigated, but could alternate electrochemical performance similar to what has been found for cathode materials for lithium-ion batteries. Within this study, we investigate RP type La2Ni0.75Co0.25O4.08 as an intercalation-based active cathode material for all-solid-state FIBs. We determine the structural changes of La2Ni0.75Co0.25O4.08 during fluoride intercalation / de-intercalation by ex-situ X-ray diffraction, which showed that F- insertion leads to transformation of the parent phase to three different phases. Changes in Ni and Co oxidation states and coordination environment were examined by X-ray absorption spectroscopy and magnetic measurements in order to understand the complex reaction behaviour of the phases in detail, showing that the two transition metals behave differently in the charging and discharging process. Under optimized operating conditions, a cycle life of 120 cycles at a critical cut-off capacity of 40 mAh g-1 against Pb/PbF2 was obtained, which is one of the highest observed for intercalation electrode materials in FIBs so far. The average Coulombic efficiencies ranged from 85% to 90%. Thus, La2Ni0.75Co0.25O4.08 could be a promising candidate for cycling-stable high-energy cathode materials for all-solid-state FIBs
Keywords: Xray

New and Facile Preparation Method for Highly Active Iron Oxide Catalysts for CO Oxidation - Schlicher, Steffen; Schoch, Roland; Prinz, Nils; Zobel, Mirijam; Bauer, Matthias (Catalysts)
This work presents a new and facile route for the preparation of iron oxide-based catalysts supported on alumina, which enables the targeted synthesis of catalysts with an increased amount of isolated tetrahedrally coordinated iron centers compared to a conventional impregnation procedure, and therefore leads to an increase in activity for CO oxidation reaction. By a multi-step impregnation–calcination protocol, the catalysts were synthesized with iron loadings of between 1 and 10 wt%, and their catalytic activity was then compared with a 10 wt% loaded catalyst prepared by conventional single impregnation. With a loading of 8 wt%, the presented catalysts showed an improved catalytic activity regarding light-off and full conversion temperatures compared to this reference. Through the application of several analytical methods (PXRD, PDF, DRUVS, SEM, XAFS), the improved catalytic activity can be correlated with an increased amount of isolated iron centers and a significantly reduced fraction of agglomerates or particles.
Keywords: Catalysis

Electronic Structure and Excited-State Dynamics of the NIR-II Emissive Molybdenum(III) Analogue to the Molecular Ruby - Kitzmann, Winald R.; Hunger, David; Reponen, Antti-Pekka M.; Förster, Christoph; Schoch, Roland; Bauer, Matthias; Feldmann, Sascha; van Slageren, Joris; Heinze, Katja (Inorganic Chemistry)
Photoactive chromium(III) complexes saw a conceptual breakthrough with the discovery of the prototypical molecular ruby mer-[Cr(ddpd)2]3+ (ddpd = N,N′-dimethyl-N,N′-dipyridin-2-ylpyridine-2,6-diamine), which shows intense long-lived near-infrared (NIR) phosphorescence from metal-centered spin-flip states. In contrast to the numerous studies on chromium(III) photophysics, only 10 luminescent molybdenum(III) complexes have been reported so far. Here, we present the synthesis and characterization of mer-MoX3(ddpd) (1, X = Cl; 2, X = Br) and cisfac-[Mo(ddpd)2]3+ (cisfac-[3]3+), an isomeric heavy homologue of the prototypical molecular ruby. For cisfac-[3]3+, we found strong zero-field splitting using magnetic susceptibility measurements and electron paramagnetic resonance spectroscopy. Electronic spectra covering the spin-forbidden transitions show that the spin-flip states in mer-1, mer-2, and cisfac-[3]3+ are much lower in energy than those in comparable chromium(III) compounds. While all three complexes show weak spin-flip phosphorescence in NIR-II, the emission of cisfac-[3]3+ peaking at 1550 nm is particularly low in energy. Femtosecond transient absorption spectroscopy reveals a short excited-state lifetime of 1.4 ns, 6 orders of magnitude shorter than that of mer-[Cr(ddpd)2]3+. Using density functional theory and ab initio multireference calculations, we break down the reasons for this disparity and derive principles for the design of future stable photoactive molybdenum(III) complexes.
Keywords: Inorganic Chemistry; Physical and Theoretical Chemistry

Janus-type emission from a cyclometalated iron(iii) complex - Steube, Jakob; Kruse, Ayla; Bokareva, Olga S.; Reuter, Thomas; Demeshko, Serhiy; Schoch, Roland; Argüello Cordero, Miguel A.; Krishna, Athul; Hohloch, Stephan; Meyer, Franc; Heinze, Katja; Kühn, Oliver; et al. (Nature Chemistry)
Abstract Although iron is a dream candidate to substitute noble metals in photoactive complexes, realization of emissive and photoactive iron compounds is demanding due to the fast deactivation of their charge-transfer states. Emissive iron compounds are scarce and dual emission has not been observed before. Here we report the Fe III complex [Fe(ImP) 2 ][PF 6 ] (HImP = 1,1′-(1,3-phenylene)bis(3-methyl-1-imidazol-2-ylidene)), showing a Janus-type dual emission from ligand-to-metal charge transfer (LMCT)- and metal-to-ligand charge transfer (MLCT)-dominated states. This behaviour is achieved by a ligand design that combines four N -heterocyclic carbenes with two cyclometalating aryl units. The low-lying π * levels of the cyclometalating units lead to energetically accessible MLCT states that cannot evolve into LMCT states. With a lifetime of 4.6 ns, the strongly reducing and oxidizing MLCT-dominated state can initiate electron transfer reactions, which could constitute a basis for future applications of iron in photoredox catalysis.
Keywords: General Chemical Engineering; General Chemistry

Understanding the Redox Mechanism of Sulfurized Poly(acrylonitrile) as Highly Rate and Cycle Stable Cathode Material for Sodium-Sulfur Batteries - Kappler, Julian; Tonbul, Güldeniz; Schoch, Roland; Murugan, Saravanakumar; Nowakowski, Michał; Lange, Pia Lena; Klostermann, Sina Vanessa; Bauer, Matthias; Schleid, Thomas; Kästner, Johannes; Buchmeiser, Michael Rudolf (Journal of The Electrochemical Society)
Room temperature sodium-sulfur (RT Na-S) batteries are considered potential candidates for stationary power storage applications due to their low cost, broad active material availability and low toxicity. Challenges, such as high volume expansion of the S-cathode upon discharge, low electronic conductivity of S as active material and herewith limited rate capability as well as the shuttling of polysulfides (PSs) as intermediates often impede the cycle stability and practical application of Na-S batteries. Sulfurized poly(acrylonitrile) (SPAN) inherently inhibits the shuttling of PSs and shows compatibility with carbonate-based electrolytes, however, its exact redox mechanism remained unclear to date. Herein, we implement a commercially available and simple electrolyte into the Na-SPAN cell chemistry and demonstrate its high rate and cycle stability. Through the application of in situ techniques utilizing electronic impedance spectroscopy (EIS) and X-ray absorption spectroscopy (XAS) at different depths of charge and discharge, an insight into SPAN’s redox chemistry is obtained.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Tethering chiral Rh diene complexes inside mesoporous solids: experimental and theoretical study of substituent, pore and linker effects on asymmetric catalysis - Kirchhof, Manuel; Gugeler, Katrin; Beurer, Ann-Katrin; Fischer, Felix Richard; Batman, Derman; Bauch, Soeren M.; Kolin, Sofia; Nicholas, Elliot; Schoch, Roland; Vogler, Charlotte; Kousik, Shravan R.; Zens, Anna; et al. (Catalysis Science Technology)
Improved enantioselectivity in the 1,2-addition was observed for chiral Rh norbornadiene catalysts immobilized on ordered mesoporous silica with small pores. Confinement effects were rationalized by experimental and computational studies.
Keywords: Catalysis

Chemical and photophysical properties of amine functionalized bis‐NHC‐pyridine‐Ru(II) complexes - Fritsch, Lorena; Vukadinovic, Yannik; Lang, Moritz; Naumann, Robert; Bertrams, Maria-Sophie; Kruse, Ayla; Schoch, Roland; Müller, Patrick; Neuba, Adam; Dierks, Philipp; Lochbrunner, Stefan; Kerzig, Christoph; et al. (ChemPhotoChem)
The effects of backbone amine functionalization in three new homoleptic C^N^C type ruthenium(II) complexes bearing a tridentate bis‐imidazole‐2‐ylidene pyridine ligand framework are characterized and studied by single crystal diffraction, electrochemistry, optical spectroscopy and transient absorption spectroscopy in combination with ab initio DFT calculations. Functionalization by dimethylamine groups in 4‐position of the pyridine backbone significantly influences the properties of the complexes as revealed by comparison with the unfunctionalized references. As a result of the amine functionalization, a higher molar absorption coefficient of the MLCT bands, a decreased photoluminescence quantum yield at room temperature together with a shortened excited state lifetime but an improved photostability is observed. Introduction of electron donating and withdrawing groups at the NHC unit modifies the electronic and optical properties, such as the oxidation potential, absorption and emission properties, and the lifetimes of the excited states.
Keywords: Photo

Iron(III)-Complexes with N-Phenylpyrazole-Based Ligands - Hirschhausen, Tanja; Fritsch, Lorena; Lux, Franziska; Steube, Jakob; Schoch, Roland; Neuba, Adam; Egold, Hans; Bauer, Matthias (Inorganics)
The use of iron as a replacement for noble metals in photochemical and photophysical applications is challenging due to the typically fast deactivation of short-lived catalytically active states. Recent success of a cyclometalated iron(III) complex utilizing a bis-tridentate ligand motif inspired the use of phenyl-1H-pyrazole as a bidentate ligand. Five complexes using the tris(1-phenylpyrazolato-N,C2)iron(III) complex scaffold are presented. In addition to the parent complex, four derivatives with functionalization in the meta-position of the phenyl ring are thoroughly investigated by single crystal diffractometry, UV-Vis-spectroscopy, and cyclic voltammetry. Advanced X-ray spectroscopy in the form of X-ray absorption and emission spectroscopy allows unique insights into the electronic structure as well as DFT calculations. The ligand design leads to overlapping MLCT and LMCT absorption bands, and emissive behavior is suppressed by low-lying MC states.
Keywords: Photo

High‐Resolution X‐ray Absorption and Emission Spectroscopy for Detailed Analysis of New CO2 Methanation Catalysts - Strübbe, Sven; Nowakowski, Michał; Schoch, Roland; Bauer, Matthias (ChemPhysChem)
Abstract A new approach for the characterization of CO 2 methanation catalysts prepared by thermal decomposition of a nickel MOF by hard X‐ray photon‐in/photon‐out spectroscopy in form of high energy resolution fluorescence detected X‐ray absorption near edge structure spectroscopy (HERFD‐XANES) and valence‐to‐core X‐ray emission (VtC‐XES) is presented. In contrast to conventional X‐ray absorption spectroscopy, the increased resolution of both methods allows a more precise phase determination of the final catalyst, which is influenced by the conditions during MOF decomposition.
Keywords: Catalysis

Single-Layer T′ Nickelates: Synthesis of the La and Pr Members and Electronic Properties across the Rare-Earth Series - Wissel, Kerstin; Bernardini, Fabio; Oh, Heesu; Vasala, Sami; Schoch, Roland; Blaschkowski, Björn; Glatzel, Pieter; Bauer, Matthias; Clemens, Oliver; Cano, Andrés (Chemistry of Materials)
Understanding high-temperature unconventional superconductivity has become a long-lasting problem in which the cuprates stand as central reference materials. Given this impasse, the recent discovery of superconductivity in analogous nickelate thin films represents a fundamental breakthrough calling for the identification of additional materials in this class. In particular, thermodynamically more robust systems are required to “upgrade” nickelate superconductors from thin films to bulk samples. Here, we contribute in this direction by reporting the synthesis of the new single-layer T′ Pr2NiO3F compound, assessing this synthesis in relation to the only previous T′ nickelate La2NiO3F, and analyzing the electronic properties across the R2NiO3F series (R = La–Lu) via first-principles calculations. We find that these mixed anion systems have a comparatively high degree of stability and their synthesis enables a fine-tuning of their composition as inferred from their characterization. Furthermore, we find that these unprecedented square-planar nickelates hold great promise as prospective superconductors due to their exceptional electronic structure.
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

Quality or Quantity? How Structural Parameters Affect Catalytic Activity of Iron Oxides for CO Oxidation - Schlicher, Steffen; Prinz, Nils; Bürger, Julius; Omlor, Andreas; Singer, Christian; Zobel, Mirijam; Schoch, Roland; Lindner, Jörg K. N.; Schünemann, Volker; Kureti, Sven; Bauer, Matthias (Catalysts)
<The replacement of noble metal catalysts by abundant iron as an active compound in CO oxidation is of ecologic and economic interest. However, improvement of their catalytic performance to the same level as state-of-the-art noble metal catalysts requires an in depth understanding of their working principle on an atomic level. As a contribution to this aim, a series of iron oxide catalysts with varying Fe loadings from 1 to 20 wt% immobilized on a γ-Al2O3 support is presented here, and a multidimensional structure–activity correlation is established. The CO oxidation activity is correlated to structural details obtained by various spectroscopic, diffraction, and microscopic methods, such as PXRD, PDF analysis, DRUVS, Mössbauer spectroscopy, STEM-EDX, and XAS. Low Fe loadings lead to less agglomerated but high percentual amounts of isolated, tetrahedrally coordinated iron oxide species, while the absolute amount of isolated species reaches its maximum at high Fe loadings. Consequently, the highest CO oxidation activity in terms of turnover frequencies can be correlated to small, finely dispersed iron oxide species with a large amount of tetrahedrally oxygen coordinated iron sites, while the overall amount of isolated iron oxide species correlates with a lower light-off temperature.
Keywords: Physical and Theoretical Chemistry; Catalysis; General Environmental Science; Key

Olefin Metathesis in Confinement: Towards Covalent Organic Framework Scaffolds for Increased Macrocyclization Selectivity - Emmerling, Sebastian T.; Ziegler, Felix; Fischer, Felix R.; Schoch, Roland; Bauer, Matthias; Plietker, Bernd; Buchmeiser, Michael R.; Lotsch, Bettina V. (Chemistry – A European Journal)
Covalent organic frameworks (COFs) offer vast structural and chemical diversity enabling a wide and growing range of applications. While COFs are well-established as heterogeneous catalysts, so far, their high and ordered porosity has scarcely been utilized to its full potential when it comes to spatially confined reactions in COF pores to alter the outcome of reactions. Here, we present a highly porous and crystalline, large-pore COF as catalytic support in α,ω-diene ring-closing metathesis reactions, leading to increased macrocyclization selectivity. COF pore-wall modification by immobilization of a Grubbs-Hoveyda-type catalyst via a mild silylation reaction provides a molecularly precise heterogeneous olefin metathesis catalyst. An increased macro(mono)cyclization (MMC) selectivity over oligomerization (O) for the heterogeneous COF-catalyst (MMC:O=1.35) of up to 51 % compared to the homogeneous catalyst (MMC:O=0.90) was observed along with a substrate-size dependency in selectivity, pointing to diffusion limitations induced by the pore confinement.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Higher MLCT lifetime of carbene iron(ii) complexes by chelate ring expansion - Reuter, Thomas; Kruse, Ayla; Schoch, Roland; Lochbrunner, Stefan; Bauer, Matthias; Heinze, Katja (Chemical Communications)
Combining strong σ-donating N-heterocyclic carbene ligands and π-accepting pyridine ligands with a high octahedricity in rigid iron(II) complexes increases the 3MLCT lifetime from 0.15 ps in the prototypical [Fe(tpy)2]2+ complex to 9.2 ps in [Fe(dpmi)2]2+12+. The tripodal CNN ligand dpmi (di(pyridine-2-yl)(3-methylimidazol-2-yl)methane) forms six-membered chelate rings with the iron(II) centre leading to close to 90° bite angles and enhanced iron-ligand orbital overlap
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Selective Benzylic CH‐Borylations by Tandem Cobalt Catalysis - Ghosh, Pradip; Schoch, Roland; Bauer, Matthias; Jacobi von Wangelin, Axel (Angewandte Chemie International Edition)
Metal-catalyzed C−H activations are environmentally and economically attractive synthetic strategies for the construction of functional molecules as they obviate the need for pre-functionalized substrates and minimize waste generation. Great challenges reside in the control of selectivities, the utilization of unbiased hydrocarbons, and the operation of atom-economical dehydrocoupling mechanisms. An especially mild borylation of benzylic CH bonds was developed with the ligand-free pre-catalyst Co[N(SiMe3)2]2 and the bench-stable and inexpensive borylation reagent B2pin2 that produces H2 as the only by-product. A full set of kinetic, spectroscopic, and preparative mechanistic studies are indicative of a tandem catalysis mechanism of CH-borylation and dehydrocoupling via molecular CoI catalysts.
Keywords: General Chemistry; Catalysis

Electrochemical Reduction and Oxidation of Ruddlesden–Popper-Type La2NiO3F2 within Fluoride-Ion Batteries - Wissel, Kerstin; Schoch, Roland; Vogel, Tobias; Donzelli, Manuel; Matveeva, Galina; Kolb, Ute; Bauer, Matthias; Slater, Peter R.; Clemens, Oliver (Chemistry of Materials)
Within this article, it is shown that an electrochemical defluorination and additional fluorination of Ruddlesden–Popper-type La2NiO3F2 is possible within all-solid-state fluoride-ion batteries. Structural changes within the reduced and oxidized phases have been examined by X-ray diffraction studies at different states of charging and discharging. The synthesis of the oxidized phase La2NiO3F2+x proved to be successful by structural analysis using both X-ray powder diffraction and automated electron diffraction tomography techniques. The structural reversibility on re-fluorinating and re-defluorinating is also demonstrated. Moreover, the influence of different sequences of consecutive reduction and oxidation steps on the formed phases has been investigated. The observed structural changes have been compared to changes in phases obtained via other topochemical modification approaches such as hydride-based reduction and oxidative fluorination using F2 gas, highlighting the potential of such electrochemical reactions as alternative synthesis routes. Furthermore, the electrochemical routes represent safe and controllable synthesis approaches for novel phases, which cannot be synthesized via other topochemical methods. Additionally, side reactions, occurring alongside the desired electrochemical reactions, have been addressed and the cycling performance has been studied.
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry